Perlindungan Hukum Bagi Perempuan Korban Kekerasan Nonfisik Dalam Rumah Tangga Menurut UU No. 23 Tahun 2004 di DKI Jakarta - Wenny Juliani; Aji Wibowo (Fakultas Hukum Universitas Tarumanagara, 2019)
The Act Num. 23/2004 about the Abolition of Domestic Violence regulates about the provision of protection and restoration for victims, which are the must given to fullfil the victims’ right, and also the criminal sanctions for perpetrators. According to the Act, this kind of violence divided into four categories, There are physical abuse, psychic abuse, sexual abuse and household neglection. By taking some data about violence against women in Jakarta, the problems formulation for this journal are: What the form of legal protection for women victims of non-physical violence in the household according to the Act Num. 23/2004 in Jakarta; and how the implementation of the legal protection for women victims of non-physical violence in the household according to the Act Num. 23/2004 in Jakarta. The method that used to write this journal is normative legal research, which is supported by some interviews with parties who do work in the field of fulfilling women's welfare and rights. In the act Num. 23/2004 there are two types of protection, they’re temporary protection and protection based on court stipulations. On the implementation, from the very first time that the protection given until the recovery, each process involves professionals in their respective fields. It is important, so that the victim can get the immidiate and right treatment. However, the implementation of the provision of protection and restoration to the victims still faces various obstacles, both in terms of substance, structure, and culture of the community.